2000
DOI: 10.1007/s12043-000-0115-0
|View full text |Cite
|
Sign up to set email alerts
|

Pressure induced phase transition behaviour in f-electron based dialuminides

Abstract: The rare-earth and actinide based compounds are endowed with several exotic physical and chemical properties due to the presence of -electrons. These properties exhibit interesting changes under the action of various thermodynamic fields and hence continues to be a subject of extensive research. For instance, under pressure, the nature of -electrons can be changed from localized to itinerant, leading to a variety of changes in their structural, physical and chemical properties. The present review on the high p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Introduction Systematic investigations of pressure-induced structural stability and possible structural sequences observed along homologues of various compounds lay the foundation for the construction of detailed high-pressure structural stability maps (Pettifor 1998, Sahu andChandra Shekar 2000). These maps have proved their usefulness by offering the means of finding correlations between various crystal structures and of predicting new structures, at both atmospheric and high pressures.…”
mentioning
confidence: 99%
“…Introduction Systematic investigations of pressure-induced structural stability and possible structural sequences observed along homologues of various compounds lay the foundation for the construction of detailed high-pressure structural stability maps (Pettifor 1998, Sahu andChandra Shekar 2000). These maps have proved their usefulness by offering the means of finding correlations between various crystal structures and of predicting new structures, at both atmospheric and high pressures.…”
mentioning
confidence: 99%
“…The rare-earth intermetallic compound cerium di-gallide crystallizes in the AlB 2 -type structure at ambient conditions with the space group symmetry P6/mmm [1][2][3][4][5]. * E-mail: yasemin@gazi.edu.tr Several similar systems exhibiting the AlB 2 -type structure was investigated by Chandra Shekar et al [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…* E-mail: yasemin@gazi.edu.tr Several similar systems exhibiting the AlB 2 -type structure was investigated by Chandra Shekar et al [1][2][3]. They found that these systems have a tendency to follow a sepecific structural sequence under pressure, namely AlB 2 (P6/mmm) to ZrSi 2 (Cmcm) to ThSi 2 (I4 1 /amd) to Cu 2 Sb (P4/nmm) type, by using X-ray diffraction techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure plays a significant role in studying the nature of f-electron based rare-earth (4f) and actinide (5f) systems [1][2][3]. In the rare-earth elements, the 4f states are localized and magnetic, whereas in the actinides, the 5f states exhibit dual nature [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…This influences the physical properties of the felectron based systems and studies on pressure effects in these systems are quite exciting [7]. Further, a systematic study of the pressure induced structural sequences has become very important in probing their electronic structure, in understanding the transition mechanisms and in predicting phase transitions [1][2][3][4]. Electronic structure calculations as function of reduced volume or pressure, on the other hand, bring out the correlations between the structural stability and phase transition behaviour in these systems with their electronic structure.…”
Section: Introductionmentioning
confidence: 99%